METHOD OF MONITORING OF STORES OF THE BOATING INSTALLATION AND IMPROVING THE EFFICIENCY OF COMMUNICATION OPERATORS OF DISTRIBUTED COMPUTERIZED SYSTEMS - Процюк, Галина Ярославівна; Николайчук, Любов Михайлівна; Возна, Наталія Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents method of monitoring state of the drilling rig ("norm", "development of the accident" and "accident") based on the calculation of statistical characteristics of controlled technological parameters and the construction of a figurative cluster model (FCM). The interaction features of the operator-computerized system based on FCM have been classified and investigated which increase the efficiency and speed of the operator’s response to the deviation of the technological process from the norm.